PELAKSANAAN LELANG EKSEKUSI PANITIA URUSAN PIUTANG NEGARA DIKOTA SAMARINDA - Risky Normelia (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT This study aims to determine the auction process carried out by PUPN execution and to determine the legal settlement in the case of participants who expressed won the auction turned out to be in default. Based on the discussion obtained is that in Act 49 of 1960, in charge of completing PUPN receivables originating from the creditor countries (Agencies-Government or State Owned Enterprises). In carrying out the tasks and processes, PUPN with the power of law is authorized to make the "Joint Statement" between Chairman PUPN by the debtor, the nature of the joint statement has value as the court verdict has to have permanent legal force, (executable). PUPN also authorized to establish and implement Forced Letter, in the form of the determination letter to: 1) Run the confiscation of execution against the assets of the Borrower; 2) Run the auction sales on properties of debtors who have been seized through the intermediary of the Office of State Auction. Hence the decision PUPN often said to be a moot court (quasi recht spraak) that is a decision that is equated with the civil judge's decision was legally binding.This research is a normative law, so the main data used is secondary data. To complement secondary data, also used primary data.Keywords: Execution, Mortgage, State Receivables